Avances en la generación de mutantes inducidas en especies forrajeras - Garcia, Araceli Nora; Gomez, Maria Cristina; Ladoux, Angeles; Landau, Alejandra Mabel; Prina, Alberto Raul; Pagano, Elba Maria (Sociedad Argentina de Genética, 2025)
Poster